AN INFLUENCE OF THE PROGRAM OF THE UNIVERSAL SPORTS SCHOOL DUBROVNIK ON THE MOTOR ABILITIES DEVELOPMENT OF SIXTH YEAR CHILDREN - Đivo Ban; Aleksandar Selmanović; Ivica Glavan (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The aim of the research was to establish the effects of the diverse kinesiology program on the motor abilities development on a random sample of an unselected population of six-year old boys and girls, i.e. 34 regular attendants of the Universal Sports School Dubrovnik, within the period of 8 months (initial and final state). The variable sample consisted of 8 motor ability evaluation tests. Seriously changes positively established of tests of explosive and repetitive strength, coordination and frequency of movement hand.